Formation of Cross-Cultural Values of Pupils - Ibraimova, Linure (Pedagogical Discourse, 2012)
The problem of cross-cultural values of students is analyzed in the article. Cross-cultural values create a process of interaction between the different types of culture and their corresponding educational practices, which were the main factor in semantic value and characteristics of modern education.